Solidworks a step-by-step tutorial - Sinclair, James A.
This e-book CD-ROM contains a selection of professionally developed video educational lessons, enabling the learner to learn the subject in the quickest and most efficient manner. This e-book is designed to provide most intuitive way of communication between the student and the computer.It's creation is based on the latest research in Human-Computer Interaction science. Because this book is developed by a Doctoral-level university professor, it may be suited as a valuable supplement to a standard educational curriculum